Conditional cash transfer programmes and gender vulnerabilities: Case studies of Brazil, Chile and Colombia - Fábio Veras Soares; Elydia Silva (International Policy Centre for Inclusive Growth (IPC-IG), 2010)
This paper analyses Brazilian, Chilean and Colombian experiences with conditional cash transfer programmes and how they have helped tackle gendered economic and social vulnerabilities. It is argued that Bolsa Família, Chile Solidario and Familias en Acción should be analysed within the broader social protection strategies in which they are meant to be components. Such an approach can help generate thinking on ways to improve the impacts of the programmes in terms of gender equality. A detailed description of the programmes' design and implementation features is provided in order to understand both their rationale and their impacts. We conclude that the programmes do tackle a number of gendered vulnerabilities but also have clear limits with regard to a more decisive role in tackling gender inequities.
Keywords: 330